Antibacterial Activity Test of Trema orientalis L. Blumae (Anggrung) Granule Extract Against Bacteria Salmonella sp with The Wet Granulation Method - Ewaldo Bonaventura Wijaya (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2020)
Diarrhea is a cause of increasing mortality in infants and toddlers around the world.  Diarrhea is a dangerous disease because it causes death and makes a case of outbreak.  In Indonesia, the Trema orientalis L. plant is known as Anggrung.  Trema orientalis L. leaves contain tannins especially polyphenols which have the ability to retain potassium which can cure ongoing diuresis.  This study aims to determine the antibacterial activity of Anggrung leaves as an antidiarrheal drug caused by bacteria that cause diarrhea, namely Salmonella sp and the preparation of granules from leaves of Trema orientalis L. (Anggrung) which can inhibit the growth of Salmonella sp.  and become an antidiarrheal drug.  The results of the research carried out namely the leaf extract of Trema orientalis L. (Anggrung) has a strong inhibitory power due to the high concentration of the extract used.  And for leaf granules Trema orientalis L. (Anggrung) preparations have a strong inhibitory power because the composition of the extract used is greater so it forms a large inhibitory zone.  From the research conducted it can be concluded that the antibacterial testing of extracts and leaf granules preparations of Trema orientalis L. (Anggrung) has antibacterial activity.